Ventilation-Perfusion Lung Scanning and the Diagnosis of Pulmonary Embolism: Improvement of Observer Agreement by the Use of a Lung Segment Reference Chart - Lensing, Anthonie W A; van Beek, Edwin J R; Demers, Christine; Tiel-van Buul, Monique M C; Yakemchuk, Valerie; van Dongen, Annemarie; Coates, Geoffrey; Ginsberg, Jeffrey S; Hirsh, Jack; ten Cate, Jan Wouter; Büller, Harry R (Thrombosis and Haemostasis, 1992)
Objective. To test the hypothesis that the systematic use of a lung segment reference chart can improve the inter- and intra-observer agreement for the interpretation of ventilation-perfusion lung scans.Design. A randomized trial.Study population. Ventilation-perfusion lung scans were obtained in a series of 220 consecutive patients with clinically suspected pulmonary embolism.Intervention. Ventilation-perfusion scans were randomly allocated to one of two series each consisting of 110 ventilation-perfusion lung scans. The first series of lung scans was interpreted according to the routine diagnostic approach, and the second series was interpreted with the mandatory use of a lung segment reference chart on which observed ventilation and perfusion defects were drawn. The two nuclear medicine physicians agreed a priori on the diagnostic criteria of the classification scheme.Measurements. Lung scans were classified as normal, non-high probability, or high probability for pulmonary embolism. The extent of disagreement between the nuclear medicine physicians (inter-observer disagreement) and the lack of internal consistency of each nuclear medicine physician (intra-observer disagreement) was assessed by the percentage disagreement and by kappa statistic.Results. Inter-observer disagreement which was 20% in the first series, decreased significantly in the second series to 7%; P = 0.003. Intra-observer disagreement for the first series was 10% and 22% for the nuclear medicine physicians, respectively. Intra-observer disagreement for the second series of lung scans decreased significantly for one nuclear medicine physician (intra-observer disagreement, 0%; P <0.01), whereas intra-observer disagreement was reduced to 10% for the other nuclear medicine physician (P = 0.09).Conclusion. Inter- and intra-observer disagreement were significantly reduced when two nuclear medicine specialists interpreted ventilation-perfusion lung scans according to the routine diagnostic approach plus the use of a lung segment reference chart. The use of the lung segment reference chart for the interpretation of lung scans is likely to improve the management of patients with clinically suspected pulmonary embolism.